2005
DOI: 10.1016/s0002-9440(10)62335-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor II Is Involved in the Proliferation Control of Medulloblastoma and Its Cerebellar Precursor Cells

Abstract: Medulloblastomas (MBs),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 41 publications
4
100
2
Order By: Relevance
“…Shh secretion by Purkinje cells drives proliferation of granule neuron precursors (CGNPs) during development of the cerebellum, and activating mutations in this pathway (for example by inactivating the Shh-antagonist PATCHED1) are associated with the desmoplastic subtype of medulloblastoma. Activating mutations in PIK3CA have been observed in medulloblastoma (Broderick et al, 2004) and PI3K/Akt signaling enhanced the proliferative effects of Shh in these cells (Hartmann et al, 2005b), in addition to increasing tumor incidence in mouse models (Rao et al, 2004). Moreover, a recent report showed loss of Pten in CGNPs, together with Shh expression, also increased medulloblastoma incidence in mice, confirming that the PI3K pathway can contribute to tumorigenesis in this pediatric malignant brain tumor (Hambardzumyan et al, 2008).…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 75%
“…Shh secretion by Purkinje cells drives proliferation of granule neuron precursors (CGNPs) during development of the cerebellum, and activating mutations in this pathway (for example by inactivating the Shh-antagonist PATCHED1) are associated with the desmoplastic subtype of medulloblastoma. Activating mutations in PIK3CA have been observed in medulloblastoma (Broderick et al, 2004) and PI3K/Akt signaling enhanced the proliferative effects of Shh in these cells (Hartmann et al, 2005b), in addition to increasing tumor incidence in mouse models (Rao et al, 2004). Moreover, a recent report showed loss of Pten in CGNPs, together with Shh expression, also increased medulloblastoma incidence in mice, confirming that the PI3K pathway can contribute to tumorigenesis in this pediatric malignant brain tumor (Hambardzumyan et al, 2008).…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 75%
“…This group of tumors is associated with inactivating mutations of the PTCH tumor suppressor gene, activating mutations of its interaction partners, and an activation of the Hedgehog-Patched signaling pathway (2 -4, 22, 23). Recent data have shown that PI3K/ AKT signaling enhances the effects of Hedgehog in these tumors and their cerebellar precursors, and that it may represent an indispensable precondition for the molecular realization of the Hedgehog signal (21,24,25). In agreement with this finding, retroviral co-overexpression of Shh and activated Akt in cerebellar neural progenitors of the mouse newborn cerebellum significantly increased the incidence of tumors compared with the incidence of tumors induced by Shh alone (7).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another recent report (26) shows that IGF2-positive medulloblastoma cells in situ are restricted to a subpopulation that displays intense Ki-67 staining and that cultured medulloblastoma-derived cells and cerebellar neuronal precursors are growth-stimulated by IGF2. Thus, IGF2 may serve as an effective mitogen to promote growth of both medulloblastomas and GBMs, two forms of central nervous system malignancies both hypothesized to arise from neural stem and/or precursor cells.…”
Section: Discussionmentioning
confidence: 99%